Lemon Oil Enhances the Anti-Rheumatic Activity of Woody Essential Oils in Formaldehyde-Induced Arthritis in Wistar Rats - Uronnachi, Emmanuel; Okpalaku, Onyinyechi; Ikeotuonye, Chidalu (Sciences of Phytochemistry, 2024)
Rheumatoid Arthritis (RA) is a major challenge, especially in the elderly. Many orthodox drugs have been helpful in managing the disease; however, deleterious side effects have been reported. Essential oils have been shown to exhibit anti-arthritic properties. This study highlights and compares the chemical composition and anti-arthritic activities of essential oils from Citrus limon, Zingiber officinale, and Curcuma longa. Twenty-seven Wister rats of both sexes were divided into 9 groups of three animals each. Acute non-immunological arthritis was induced by a sub-plantar injection of 0.1 mL formaldehyde (2% v/v). The animals were treated topically with essential oils extracted by hydro-distillation and analyzed by gas chromatography. Measurement of paw volumes was done daily for 10 days using the volume displacement method. Ginger oil and turmeric oil achieved a 100% reduction in paw volume from the 8th day (p<0.05). The coconut oil as carrier for the essential oils exhibited sub-optimal reductions when administered alone as a control. Combinations of the oils showed an antagonistic effect in the ginger/turmeric oil blend, while the essential blends of turmeric/lemon and ginger/lemon oil performed better than the individual oils. The findings from this study showed that the woody essential oils (ginger and turmeric) exhibited the greatest anti-arthritic activity of all the oil treatment groups. Terpenes like ar-turmerone, turmerone, zingiberene, and D-limonene may have been responsible for the activities observed with the turmeric, ginger, and lemon essential oils, respectively. Lemon, ginger, and turmeric essential oils are effective for the management of rheumatoid arthritis.